Storage Time and DNA Quality Determine BRCA1/2 Sequencing Success in Prostate Cancer: A Multicentre Analysis with Therapeutic Implications - Vescovo, Mariavittoria; Raspollini, Maria Rosaria; Nibid, Lorenzo; Castiglione, Francesca; Nardi, Eleonora; de Biase, Dario; Massari, Francesco; Giunchi, Francesca; Pepe, Francesco; Troncone, Giancarlo; Malapelle, Umberto; Carosi, Mariantonia; et al. (Cancers, 2025)
Background: Approximately 25.0% of metastatic prostate cancer patients harbour DNA damage repair mutations, including BRCA1 and BRCA2, which are actionable targets for poly(ADP-ribose) polymerase (PARP) inhibitors. Accurate detection of BRCA1/2 mutations is critical for guiding targeted therapies, but crucial pre-analytical factors, such as tissue storage duration and DNA fragmentation, drastically affect the reliability of next-generation sequencing (NGS) using real-world diagnostic specimens. Methods: This multicentre study analysed 954 formalin-fixed paraffin-embedded tissue samples from 11 centres, including 559 biopsies and 395 surgical specimens. This study examined the impact of storage duration (<1 year, 1–2 years, and >2 years) and DNA parameters (concentration and fragmentation index) on NGS success rates. Logistic regression and Cox regression analyses were used to assess correlations between these factors and sequencing outcomes. Results: NGS success rates decreased significantly with longer storage, from 87.8% (<1 year) to 69.1% (>2 years). Samples with higher DNA concentrations and fragmentation indexes had higher success rates (p < 0.001). Surgical specimens had superior success rates (83.3%) compared with biopsies (72.8%) due to better DNA quality. The DNA degradation rate was more pronounced in older samples, underscoring the negative impact of extended storage. Conclusions: Timely testing of BRCA1/2 mutations is critical for optimizing the identification of prostate cancer patients eligible for PARP inhibitors. Surgical specimens provide more reliable results than biopsies and minimizing the storage duration significantly enhances testing outcomes. Standardizing pre-analytical and laboratory procedures across centres is essential to ensure personalized treatments and improve patient outcomes.